2009
DOI: 10.1186/1532-429x-11-20
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of iron chelator regimes in reducing cardiac and hepatic iron in patients with thalassaemia major: a clinical observational study

Abstract: Background: Available iron chelation regimes in thalassaemia may achieve different changes in cardiac and hepatic iron as assessed by MR. The aim of this study was to assess the efficacy of four available iron chelator regimes in 232 thalassaemia major patients by assessing the rate of change in repeated measurements of cardiac and hepatic MR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
66
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 35 publications
5
66
0
3
Order By: Relevance
“…14,15 In a study of 467 de novo MDS patients, the development of red blood cell transfusion need was associated with significantly shorter overall and leukemia-free survival in myelodysplastic syndromes without excess blasts. 16 Subsequently, a dynamic prognostic model that…”
Section: Prognostic Relevance Of Anemia and Transfusion Dependency Inmentioning
confidence: 99%
See 1 more Smart Citation
“…14,15 In a study of 467 de novo MDS patients, the development of red blood cell transfusion need was associated with significantly shorter overall and leukemia-free survival in myelodysplastic syndromes without excess blasts. 16 Subsequently, a dynamic prognostic model that…”
Section: Prognostic Relevance Of Anemia and Transfusion Dependency Inmentioning
confidence: 99%
“…15 The data from this MIOT study are also very consistent with results that were published from the same unit in Athens that showed superiority of deferiprone and combination of deferiprone and desferrioxamine over desferrioxamine and deferasirox with respect to clearance of cardiac iron. 16 Another recent Italian study concluded that, when deferiprone is used, cardiac improvement is seen before there is a significant reduction in the total body iron. 17 The theoretical mechanism for the cardiac protective effect of deferiprone is related to its chemical characteristics, including its small molecular weight.…”
mentioning
confidence: 99%
“…In one of our units it has been shown, as with a Sardinian study, that deferoxamine and deferiprone combination therapy is a powerful option for reducing cardiac iron (19,20). Our results on the effect of MRI, combined with the information from the two latter studies, as well as the study showing risk according to T2* if no changes to chelation are made (16), indicate that the beneficial effect of intensification of chelation therapy including deferoxamine and deferiprone combination therapy may be maximized when it is introduced in a timely manner.…”
Section: Discussionmentioning
confidence: 88%
“…49 In line with these trials, TDT patients treated with combination of DFO and DFP showed significantly lower risk of heart failure than the patients who were chelated with DFO alone. [50][51][52] Using combinational chelation therapy of DFP and DFO resulted in better LVEF compared to DFO monotherapy. 53 Nevertheless, less willingness of TDT patients toward using DFP is its higher rate of adverse effects.…”
Section: Preventive Measuresmentioning
confidence: 99%